Sulfur‐Bridged BODIPY DYEmers. Issue 34 (10th July 2013) - Ahrens, Johannes; Böker, Birte; Brandhorst, Kai; Funk, Markus; Bröring, Martin
Abstract Reactions of BODIPY monomers with sulfur nucleophiles and electrophiles result in the formation of new BODIPY dimers. Mono‐ and disulfur bridges are established, and the new dyestuff molecules were studied with respect to their structural, optical, and electrochemical properties. X‐ray diffraction analyses reveal individual angulated orientations of the BODIPY subunits in all cases. DFT calculations provide solution conformers of the DYEmers which deviate in a specific manner from the crystallographic results. Clear exciton‐like splittings are observed in the absorption spectra, with maxima at up to 628 nm, in combination with the expected weak fluorescence in polar solvents. A strong communication between the BODIPY subunits was detected by cyclic voltammetry, where two separated one‐electron oxidation and reduction waves with peak‐to‐peak potential differences of 120–400 mV are observed. The qualitative applicability of the exciton model by Kasha for the interpretation of the absorption spectral shape with respect to the conformational state, subunit orientation and distance, and conjugation through the different sulfur bridges, is discussed in detail for the new BODIPY derivatives. This work is part of our concept of DYEmers, where the covalent oligomerisation of BODIPY‐type dye molecules with close distances is leading to new functional dyes with predictable properties.